Evaluating Agricultural Sustainability in Permaculture Farms: A Multidimensional Approach for Resilient Farming Systems - Fatiha Hakimi; Loubna El Kihal; Mustapha El Janati; Ishtiaq Ahmad; Mourad Arabi; Muhammad Farooq (Caraka Tani: Journal of Sustainable Agriculture, 2025)
Morocco’s agriculture is increasingly constrained by climate change, water scarcity, and soil degradation, limiting the effectiveness of conventional farming. Permaculture offers a promising alternative, yet its sustainability in the Moroccan context remains underexplored. This study evaluates the multidimensional sustainability of permaculture farms and identifies key constraints to their resilience, assessing 20 farms in the commune of Brachoua using the IDEA (Indicators of Sustainability of Agricultural Farms) framework, adapted to local conditions through expert and farmer consultation. Scores were calculated across agroecological, socio-territorial, and economic dimensions. Farm typologies were identified using principal component analysis (PCA), with adequacy confirmed by eigenvalues, Kaiser-Meyer-Olkin (KMO), and Bartlett’s test, and hierarchical ascending classification (HAC), validated by dendrogram structure and silhouette index. Results show strong agroecological performance (65.1±8.51 points), moderate economic sustainability (61.0±13.53), and weak socio-territorial integration (41.1±12.19). PCA revealed two main axes explaining 85.4% of variance, while HAC distinguished two farm clusters: a small group of high-performing farms with stronger socio-territorial and economic linkages, and a majority cluster with average but uniform profiles. Weaknesses include limited livestock diversity, poor soil and water management, lack of product traceability, and weak community participation. The study concludes that while permaculture supports ecological sustainability and financial independence, socio-territorial deficiencies remain the main barrier. Targeted interventions (farmer training, cooperative development, and quality certification) are needed to improve outcomes. More broadly, the study shows the usefulness of combining IDEA with multivariate statistics to generate farm typologies, offering a transferable framework for assessing sustainability in smallholder systems facing climatic and resource challenges.